Analisis Perbedaan Hasil Belajar Peserta Didik dengan Media Dakonic dan Sempotron dalam Pembelajaran Sistem Periodik Unsur - Permatasari, Afita; Piola Naretin Rahayu, Inka; Kautsar Althaf D.I.H, Salsabila; Puji Astuti, Andari (UIR Press, 2025)
This study aims to analyze the differences in student learning outcomes using Dakonic (Chemistry Dakon) and Sempotron (Electronic Abacus) media in learning the periodic system of elements. The research employed a quantitative method with a quasi-experimental design using the Nonequivalent Control Group Design. The subjects consisted of 72 tenth-grade students of SMA Negeri 15 Semarang, divided into a control class using Sempotron and an experimental class using Dakonic. The research instrument was a learning outcome test that had been validated and tested for reliability. Data were analyzed through normality test, homogeneity test, N-Gain, and t-test. The results showed that the experimental class obtained an average N-Gain of 0.701 (high category), while the control class only reached 0.479 (medium category). The t-test also revealed a significant difference between the two classes with a significance value of 0.000 (<0.05). These findings indicate that Dakonic is more effective in improving students’ understanding of the periodic system of elements compared to Sempotron. Therefore, Dakonic can be considered as an innovative, engaging, and culturally relevant chemistry learning medium